2021
DOI: 10.5539/jel.v10n2p28
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Omani EFL Students’ Perceptions of the Newly Adopted Online Learning Platforms at the University of Technology and Applied Sciences-Salalah

Abstract: Due to the rapid advancement of the relevant technology and the COVID-19 health pandemic, educational institutions have had to adapt to ongoing and ever-changing circumstances at a very rapid rate. Thus, the Moodle and Microsoft Teams platforms are being used by teachers to more directly teach students, as well as fulfilling its initial role in providing a supplementary tool to maintain, the convention of independent learning. The current study explores the perceptions of a group of Omani students who are curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Other studies by the same author (2022a) and (2022b) at UTAS-Ibra, Oman, confirmed that online teaching via digital tools positively affects teaching and learning. Findings of the research conducted by Kashoob (2021), andAlameri et al (2020) validated that MS Teams and Moodle have been very conducive to motivating students and promoting self-study among students. Another study by Ali et al (2021) at UTAS-Ibra, Oman, suggested that My ELT has played a crucial role in helping students gain more knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies by the same author (2022a) and (2022b) at UTAS-Ibra, Oman, confirmed that online teaching via digital tools positively affects teaching and learning. Findings of the research conducted by Kashoob (2021), andAlameri et al (2020) validated that MS Teams and Moodle have been very conducive to motivating students and promoting self-study among students. Another study by Ali et al (2021) at UTAS-Ibra, Oman, suggested that My ELT has played a crucial role in helping students gain more knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…" (p. 31). A similar study by Kashoob (2021) explored Omani EFL Students' Perceptions of the Newly Adopted Online Learning Platforms at the University of Technology and Applied Sciences-Salalah. The findings of the study suggested that "the online learning environment is very conducive in motivating them towards learning English through an admittedly complex and challenging framework, that not all members of a learning community can take Arab World English Journal www.awej.org ISSN: 2229-9327 366 comprehensive advantage of."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online learning is employed through self-paced independent study units, asynchronous interactive sessions, and synchronous interactive meetings (Kashoob1 & Attamimi, 2021). Thus, learning has become flexible and accessible to university students who learn virtually both online and offline via student portals (Houlden & Veletsianos, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other articles describe Teams characteristics but fail to provide data-based analysis. For example, Kashoob and Attamimi (2021) report on using Teams and Moodle to support language learning. The article introduces both platforms in detail but does not specify how they are used in teaching.…”
Section: Teamsmentioning
confidence: 99%